Robots and the skill premium: An automation-based explanation of wage inequality - Clemens Lankisch; Klaus Prettner; Alexia Prskawetz (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2017)
We analyze the effects of automation on the wages of high-skilled and low-skilled workers and thereby on the evolution of wage inequality. Our model explains the simultaneous presence of i) increasing per capita income, ii) declining real wages of low-skilled workers, and iii) an increasing skill-premium. These developments are consistent with the experience in the United States over the past decades.
Keywords: O11; O41; I24; 330; automation; declining wages of low-skilled workers; wage inequality; skill premium; long-run growth